Другий південнослов’янський вплив у «Слові о полку Ігоревім» і «Задонщыне» - Франчук, В.Ю. (Мовознавство, 2018)
У статті здійснено спробу відновити первісні форми тих лексем «Слова о полку Ігоревім», що зустрічаються в «Задонщине» — пам’ятці, відомі списки якої належать до XV–XVII ст. Реконструйований на основі цих списків початковий текст «Задонщины» дозволяє припустити, що її автор був знайомий з тим списком «Слова», який ще не зазнав другого південнослов’янського впливу. This paper aims at reconstructing the initial forms of those lexemes from «The Tale
of Igor`s Campaign» which can be found in «Zadonshchyna» (the written records of the
latter go back to the 15th–17th centuries). The comparative analysis shows that the author of
«Zadonshchina» was acquainted with the record of «The Tale» which had not experienced
the second Southern Slavic influence yet. It means that it was created earlier than estimated
by the supporters of its later origin. The number of Southern Slavic forms increases
only during transcription and editing of both works, which corresponds to the general
tendencies of the development of East Slavic languages.